Supplementation of Black Soldier Fly (Hermetia illucens) on Activity and Capacity Phagocytic Macrophage of Laying Hens - Andri Cahya Irawan (Jurnal Ilmu Ternak dan Veteriner, 2019)
Black Soldier Fly are natural antibiotics. It is expected that the use of BSF larvae in poultry rations as an alternative source of conventional protein will contribute to improving the immune status and maintaining animal health, thereby reducing the use of antibiotic growth promoters (AGPs). This study aimed to evaluate the effect of the best type of BSF protein for determining the health status of laying hens based on the activity and capacity of macrophage phagocytosis on the non-protein A bacterium Staphyllococcus aureus. Results of this study indicated that the BSF extract (P3) has the highest phagocytic capacity value. This result proves that the BSF extract can induce macrophage cells to optimally process bacterial cells or foreign phagocyte particles. The highest average activity value, and phagocytic capacity of peritoneal macrophages was resulted from BSF extract (P3), respectively was 91.34 ± 0.38% and 22.84 macrophage-1 bacteria.